2015
DOI: 10.1159/000440841
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Genetic Architecture of Alzheimer's Disease: Where Next?

Abstract: Background: Late-onset Alzheimer's disease is a genetically complex disorder. For 17 years, APOE was the only known susceptibility gene for disease. Through mostly genome-wide association studies, 25 loci are now known to associate with late-onset Alzheimer's disease. These susceptibility loci are not randomly distributed with respect to their functions. In fact, pathway analysis implicates significant enrichment of immunity, endocytosis, cholesterol metabolism, and ubiquitination in disease. Summary: Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
(54 reference statements)
2
12
0
Order By: Relevance
“…At 60% AD risk, APOE ε3/3 individuals in the first decile of the PHS have an expected age of onset of 85 y, whereas for individuals in the tenth decile of the PHS, the expected age of onset is greater than 95 y. These findings are directly relevant to the general population, where APOE ε4 accounts for only a fraction of AD risk [3], and are consistent with prior work [26] indicating that AD is a polygenic disease where non- APOE genetic variants contribute significantly to disease etiology.…”
Section: Discussionsupporting
confidence: 86%
“…At 60% AD risk, APOE ε3/3 individuals in the first decile of the PHS have an expected age of onset of 85 y, whereas for individuals in the tenth decile of the PHS, the expected age of onset is greater than 95 y. These findings are directly relevant to the general population, where APOE ε4 accounts for only a fraction of AD risk [3], and are consistent with prior work [26] indicating that AD is a polygenic disease where non- APOE genetic variants contribute significantly to disease etiology.…”
Section: Discussionsupporting
confidence: 86%
“…At 60% AD risk APOE ε3/3 individuals in the 1 st decile of PHS have an expected age of onset of 85 whereas for individuals in the 10 th decile of PHS, the expected age of onset is greater than 95. These findings are directly relevant to the general population where APOE ε4 only accounts for a fraction of AD risk 3 and are consistent with prior work 21 indicating that AD is a polygenic disease where non- APOE genetic variants contribute significantly to disease etiology.…”
Section: Discussionsupporting
confidence: 90%
“…Although ApoE remains the most potent susceptibility gene, the advent of genome wide association studies have identified 25 loci known to associate with late-onset sporadic AD, and the advent of polygenic risk scores are now available and will further refine our understanding of genetic contributions to AD progression (for review, see Sims & Williams, 2016). …”
Section: The 1990s: Neuropsychological Characterization Of Alzheimer’mentioning
confidence: 99%